Incorporating Sustainability and Green Design Concepts into Engineering and Technology Curricula - Radian G. Belu; Richard Chiou; Lucian Ionel Cioca; Bill Tseng (Intelektual Pustaka Media Utama, 2016)
Human society is facing an uncertain future due to the present day unsustainable use of natural resources and the growing imbalance with our natural environment. Sustainability is an endeavour with uncertain outcomes requiring collaboration, teamwork, and abilities to work with respect and learn from other disciplines and professions, as well as with governments, local communities, political and civic organizations. The creation of a sustainable society is a complex and multi-stage endeavour that will dominate twenty first century. Sustainability has four basic aspects: environment, technology, economy, and societal organization. Schools with undergraduate engineering or engineering technology programs are working to include sustainability and green design concepts into their curricula. Teaching sustainability and green design has increasingly become an essential feature of the present day engineering education. It applies to all of engineering, as all engineered systems interact with the environment in complex and important ways. Our project main goals are to provide the students with multiple and comprehensive exposures, to what it mean to have a sustainable mindset and to facilitate the development of the passion and the skills to integrate sustainable practices into engineering tools and methods. In this study we are describing our approaches to incorporating sustainability and green design into our undergraduate curricula and to list a variety of existing resources that can easily be adopted or adapted by our faculty for this purpose. Our approaches are: (1) redesigning existing courses through development of new curricular materials that still meet the objectives of the original course and (2) developing upper division elective courses that address specific topics related to sustainability, green design, green manufacturing and life-cycle assessment.